2013
DOI: 10.5173/ceju.2013.01.art12
|View full text |Cite
|
Sign up to set email alerts
|

Adult Wilms’ tumor – diagnosis and current therapy

Abstract: IntroductionWilms’ tumour is one of the commonest malignant tumours of childhood. It appears mainly in the first 5 years of life. Incidental examples of nephroblastoma in adults have been described in literature (about 3% of all described cases). There are diagnostic and therapeutic difficulties in that older age group. The preoperative diagnosis of nephroblastoma in adults is difficult because there are no specific radiographic findings that allow to distinguished it from the more common adult renal tumors. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Surprisingly, WT is correlated with congenital conditions while not associated with genetic syndromes, including urogenital malformations and mental retardation [Amirian, ]. Currently, the treatment for WT includes chemotherapy before the operation and subsequent surgery, as well as postoperative adjuvant therapy [Huszno et al, ]. Overall, the survival rate for WT reaches approximately 90%, but patients usually exhibit poor clinical prognosis if diffusely anaplastic or unfavorable histology is present [Amirian, ; Zhang et al, ].…”
mentioning
confidence: 99%
“…Surprisingly, WT is correlated with congenital conditions while not associated with genetic syndromes, including urogenital malformations and mental retardation [Amirian, ]. Currently, the treatment for WT includes chemotherapy before the operation and subsequent surgery, as well as postoperative adjuvant therapy [Huszno et al, ]. Overall, the survival rate for WT reaches approximately 90%, but patients usually exhibit poor clinical prognosis if diffusely anaplastic or unfavorable histology is present [Amirian, ; Zhang et al, ].…”
mentioning
confidence: 99%
“…The spectrum of histopathological morphology is the same for nephroblastomas of adulthood and childhood as both of them constitute the same entity, but schemes of postoperative therapy harbor greater toxicity in adults than in children [1]. The case presented by us showed a blastemal dominant histology in spite of the fact that epithelial type is themostcommoninadultnephroblastoma [14].In addition,thehighnumberofmitoses(8mitosesper 1HPF)definitelyexceedsthenumberof20mitoses per10HPF,andthethresholdofover20mitoseswas a feature found exclusively in intermediate or high risknephroblastomasandwasadditionallycorrelated with CD44 expression in a study of 39 cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…Wilms' tumor is a common malignant neoplasm ofchildhood,whileitisincidentalinadulthoodwith afrequencyofapproximately3%ofallreportedcases [1].OnsetofbothchildhoodandadultWilms'tumor isprecededbymutationoftheWT1gene [2].However,WT1mutationsaredetectedinonly10%upto 15%ofpediatricWilms'tumors.Inaddition,adult Wilms' tumor was also reported to harbor a novel germline mutation in intron 1 of WT1: IVS1-6 C-->A [2].Incontrasttopediatrictumors,thepreoperativedetectionofadultWilms'tumor(AWT)is particularlyworrisomeasradiologicalimagingisnot specificenoughtodistinguishnephroblastomafrom the more frequent renal cancers of adulthood [1].…”
Section: Introductionmentioning
confidence: 99%
“…spontaneous rupture of adult Wilms' tumor Treatment guidelines in adults have not been established, most authors suggest adult patients can be treated according to pediatric protocols. 6 Radical nephrectomy is the treatment of choice for one-sided nephroblastoma. Multiple studies have demonstrated that laparoscopic renal surgery provides recuperative and cosmetic advantages in contrast to open surgery.…”
Section: Discussionmentioning
confidence: 99%